BLUESCHISTS, ECLOGITES, OPHIOLITES AND SUTURE ZONES IN NORTHWEST TURKEY: A REVIEW AND A FIELD EXCURSION GUIDE - Okay, Aral I.; Whitney, Donna L. (Ofioliti, 2010)
The Tavsanli Zone in western and south-central Turkey constitutes one of the largest and best preserved high-pressure metamorphic belts in the world. Blueschists and scarce lawsonite-eclogites crop out in an east-west-rending zone, 50-60 km wide and about 250 km long, and are tectonically overlain by an oceanic accretionary complex and large ophiolite slabs. Undeformed Early to Middle Eocene granodiorites (ca. 50 Ma 40Ar/39Ar isochron ages), intrude the blueschists and the overlying ophiolite. The blueschists of the Tavsanli Zone represent the subducted north-facing passive continental margin of the Anatolide- Tauride block. They were partly exposed by, or were at high crustal levels during the latest Cretaceous, prior to the Paleocene continent-continent collision. The blueschists of the Tavsanli Zone comprise a variety of metasedimentary and metamagmatic lithologies. The metasedimentary sequence, originally deposited on continental crust, comprise a schist-marble series of Mesozoic age with peak pressure and temperatures of 24 kbar and 430-500°C, respectively, and with Late Cretaceous (ca. 80 Ma) metamorphic ages. The oceanic lithologies are made up mainly of metabasites with metacherts, phyllites, which have undergone metamorphism from incipient blueschist facies to lawsonite-eclogite facies. The guide, prepared for a three-day field trip, provides information on the tectonic setting, tectonostratigraphy, petrology, and geological evolution of the Tavsanli Zone blueschists and lawsonite-eclogites followed by detailed description of the field stops. It also includes data on the Triassic blueschists and eclogites from north of the Tavsanli Zone.